Tafsir Tarbawi Surat Al-Kahfi Perspektif Pendidikan Pesantren: Qur’anic Educational Interpretation of Chapter Al-Kahf from the Perspective of Pesantren Education - Rosidin, Rosidin (RABBAYANI: Jurnal Pendidikan dan Peradaban Islami, 2023)
This article offers four ideas about strategy of creating educational environment to develop pesantren based on library research of education values that contained in Surah al-Kahfi through implementation of Tafsir Tarbawi methods. First, pesantren organize regeneration program through creating of religious culture and educational interaction. Religious culture to invite the grace (rahmat) of Allah which serves as protection of learners from social interaction pollution; whereas educational interaction to develop maturity or independence of learners through recognition, imitation and application. Second, pesantren optimizing economic capital and social capital. Optimization of economic capital through realization of pesantren’s function as a center of public economy, while optimizing social capital through realization of pesantren’s function as a social institution. Third, pesantren organize quality education that is supported by dedicated teachers and students, and curriculum that educate social justice, social faith and social welfare. Fourth. Leadership and management of pesantren supported by projective and proactive attitude. Projective attitude is based on vision of reading the signs of circumtances, while the proactive attitude is realization of the projective vision at the level of policy and implementation. Tulisan ini menawarkan empat strategi penciptaan lingkungan edukatif untuk pengembangan pesantren berdasarkan hasil telaah nilai-nilai tarbawi yang terkandung dalam Surat al-Kahfi melalui implementasi metode tafsir tarbawi. Pertama, pesantren menyelenggarakan program regenerasi melalui penciptaan budaya religius dan interaksi edukatif. Budaya religius untuk mengundang rahmat Allah SWT sebagai proteksi peserta didik dari polusi interaksi sosial; sedangkan interaksi edukatif untuk mengembangkan kemandirian peserta didik melalui i’tiraf, imtitsal, ittiba’. Kedua, pesantren mengoptimalkan kapital ekonomi dan sosial. Optimalisasi kapital ekonomi melalui realisasi fungsi pesantren sebagai pusat ekonomi masyarakat, sedangkan optimalisasi kapital sosial melalui realisasi fungsi pesantren sebagai institusi sosial. Ketiga, pesantren menyelenggarakan pendidikan berkualitas yang didukung pendidik dan peserta didik yang berdedikasi tinggi serta kurikulum yang mendidikkan keadilan, keimanan dan kesejahteraan sosial. Keempat. Kepemimpinan dan manajemen pesantren yang didukung sikap proyektif dan proaktif. Sikap proyektif didasarkan pada visi membaca tanda-tanda zaman secara responsif, sedangkan sikap proaktif merupakan realisasi dari visi proyektif pada tataran kebijakan dan pelaksanaan. Kata Kunci: Pengembangan Pesantren, Pendidikan Pesantren, Nilai-nilai Tarbawi, Surat al-Kahfi.